PEMODELAN FIXED TIME PERIOD UNTUK SISTEM PENGENDALIAN PERSEDIAAN PADA GUDANG REGIONAL - Taufik Djatna; Bagas Ari Wicaksono (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Inventory control modelling is utilized to optimize warehousing cost and the availability of product and raw material while keeping customer satisfaction level. A formulation of fuzzy time series based on raw material planning for fixed-time period safety stock model was proposed to enhance forecasting accuracy in limited data availability. Safety stock levels were computed in monthly fashion to optimizing the most appropriate capacity in each regional warehouse. Forecasting accuracy was based on MAPE indicator. By deploying forecasted data, the calculation of product quantity and capacity level were set to correspond with the target of product box quantity to produce. The result showed that the forecasting of six products in four regions showed the range of MAPE values with minimum at 0.29% and maximum at 1.94% level. The implementation of formula on a real field application had increased the data flow transaction and mobility amount among stakeholders. Keywords: formulation, fuzzy tim series forecasting, inventory control, modelling, MAPE